Circular Approaches in Small-Scale Food Production - Petra Schneider; Vincent Rochell; Kay Plat; Alexander Jaworski (Circular Economy and Sustainability, 2021)
Globally, food production is one of the main water and energy consumers. Having in view the growing population on global scale, a higher efficiency of food production is needed. Circular approaches offer a large potential to enhance the efficiency of food production and have a long tradition in the food production process of mankind. However, industrial farming has interdicted traditional cycle-closed farming approaches leading to a variety of environmental challenges. The contribution illustrates the basics of traditional gardening and farming approaches and describes how their characteristics are adapted in innovative modern farming systems like aquaponic, permaculture, urban farming, as well as recovered traditional farming systems. The approach to combine traditional farming methods with modern ones will provide multiple benefits in the future to ensure food security. There is to be underlined that such a strategy holds a substantial potential of circular flux management in small scale food production. This potential could be transposed to a larger scale also, particularly in terms of agroforestry and integrated plant and animal husbandry or integrated agriculture and aquaculture. In this way, small-scale food production holds a large potential for the future implementation of the water-energy-food security nexus.
Keywords: 330; Traditional food production; Small-scale food production; Circular gardening; Integrated agroecology; Urban farming; Controlled environment agriculture